2007
DOI: 10.1016/j.febslet.2007.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and insulin resistance

Abstract: Obesity-induced chronic inflammation is a key component in the pathogenesis of insulin resistance and the Metabolic syndrome. In this review, we focus on the interconnection between obesity, inflammation and insulin resistance. Proinflammatory cytokines can cause insulin resistance in adipose tissue, skeletal muscle and liver by inhibiting insulin signal transduction. The sources of cytokines in insulin resistant states are the insulin target tissue themselves, primarily fat and liver, but to a larger extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
727
2
18

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 914 publications
(765 citation statements)
references
References 70 publications
18
727
2
18
Order By: Relevance
“…Chronic obesity has been correlated with the development of liver disease owing to prolonged, mild inflammation induced by obesity [36,37]. iNOS is an inflammatory mediator that promotes the production of reactive oxygen species, NO, and endogenous signalling molecules, which contribute towards prolonging mild systemic inflammation in the liver of HFD-fed obese mice [38], which subsequently contributes to the pathogenesis of HFD-induced insulin resistance [39]. Previous studies have shown that vinegar has an anti-inflammatory effect on paracetamol-induced liver damage in mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obesity has been correlated with the development of liver disease owing to prolonged, mild inflammation induced by obesity [36,37]. iNOS is an inflammatory mediator that promotes the production of reactive oxygen species, NO, and endogenous signalling molecules, which contribute towards prolonging mild systemic inflammation in the liver of HFD-fed obese mice [38], which subsequently contributes to the pathogenesis of HFD-induced insulin resistance [39]. Previous studies have shown that vinegar has an anti-inflammatory effect on paracetamol-induced liver damage in mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is a pleiotropic hormone that regulates several cell functions among which stimulation of glucose transport, cell growth, energy balance and regulation of gene expression (de Luca and Olefsky, 2008). Insulin initiates its action through binding to the insulin receptor which results into dimerization and autophosphorylation of this insulin receptor.…”
Section: Insulin Resistance: a Critical Node Between Mets And Nafldmentioning
confidence: 99%
“…It signals via the tyrosine phosphorylation of the insulin receptor substrate molecule, which subsequently activates a cascade of intracellular signalling events. Insulin activates two main signalling pathways one of which is phosphatidylinositol-3-kinase-AKT pathway primarily responsible for mediating glucose uptake (14,15) . Upon insulin stimulation, the GLUT-4 promptly translocates from intracellular storage sites to the plasma membrane, facilitating glucose uptake (16,17) .…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%